Use of early pulse oximetry in the detection of cardiac lesions among asymptomatic term newborns - Atef El-Sayed Donia; Omar Atef Tolba (SpringerOpen, 2016)
Background and objectives: Cardiovascular malformations are the commonest form of congenital defects and could result in significant morbidity. Antenatal and early postnatal detection is still unreliable, especially in developing countries and low-income communities. The aim of the study was to assess the value of early pulse oximetry in the detection of cardiac lesions among asymptomatic term newborns with subnormal oxygen saturation. Patients and methods: A cross-sectional study was conducted at the well-baby nursery of a community hospital, between March and August 2013. A total of 120 asymptomatic, apparently healthy term newborns who had persistent postductal SpO2 < 95% in the initial and repeat tests within the first 24 h after birth were consecutively enrolled. Pulse oximetry testing was performed after the age of 2 h and confirmed 2 h later. Cases with persistent saturation below 95% underwent echocardiography. Results: Significant cardiac lesions were detected in 38 newborns (31.6%); they had significantly lower oxygen saturation compared to those with insignificant lesions (n = 41, 34.2%) and normal hearts (n = 41, 34.2%). Repeat testing after 2 h was more reliable. Using cut-offs lower than 95% missed a significant number of lesions. Conclusion: Pulse oximetry can be used as a tool in apparently healthy term newborns for the early detection of cardiac lesions that might necessitate specialized follow-up and care. An initial test after the age of 2 h followed by a confirmatory test 2 h later, with a cut-off value of <95% is proposed. A comprehensive study is necessary to validate the results of this study. This might be of significant importance in low-income communities.